Argumentation and polyphony in encapsulating anaphors - Cavalcante, Mônica Magalhães (2011)
The paper applies to the encapsulated anaphors the lexical description carried out within the Semantic Blocks Theory (Ducrot, 2001) and the Polyphony Theory (Ducrot & Carel, 2008). By arguing on the secondary role that literature on such referential process gives to the argumentative-polyphonic phenomenon, the study makes use of an argumentative approach, in what argumentative chaining derives from a linguistic strategy articulated by the speaker based on his\her project of saying. Under such point of view, depending on speaker’s attitudes, anaphoric signing scaffolds argumentative meaning for the chaining.